Investigating colloid-associated transport of cadmium and lead in a clayey soil under preferential flow conditions - Wenjie Zhang (IWA Publishing, 2021)
Colloids have a high adsorption capacity and can be mobile under preferential flow, and so may facilitate heavy metal migration. Heavy metal migration with soil colloids in a clayey soil under preferential flow conditions was investigated through experiments. Adsorption tests were carried out to determine the adsorption of Cd2+ and Pb2+ to the clay and colloids. The preferential flow characteristics in the soil column were investigated by dye tracing tests. The mobility of soil colloids in the soil column was studied by breakthrough tests. Leaching tests of cadmium and lead with and without colloids were carried out. The adsorption tests showed that soil colloids adsorbed more cadmium and lead than the silty clay. The dye tracing tests showed that moderate preferential flow in the soil column can be obtained by choosing clod-size distribution and dry density. The co-leaching test showed that the outflow of cadmium and lead was 1.49 and 33.88 times greater with colloids than without, respectively. The heavy metals adsorbed onto clay and the pore concentrations were both lower with colloids than without, indicating more heavy metals migrated downward with colloids. The migration of cadmium and lead was greatly enhanced by colloids under preferential flow conditions. HIGHLIGHTS Soil columns with preferential flow path were constructed with soil clods.; Preferential flow in the soil column was investigated by dye tracing tests.; The mobility of soil colloids in the soil column was studied.; Leaching tests of Cd2+ and Pb2+ with and without colloids were carried out.; Breakthrough curves, the adsorbed heavy metals and pore solution concentrations were analyzed.;